Cooperation of the European Union and Japan on climate and climate neutrality - Kisiel, Adrianna; Kukieła, Julia (Destined to Cooperate? Various Dimensions of European Union Policy Towards Asian Countries, 2024)
The effects of global warming pose a huge threat to the entire planet. The European Union has been trying to stop climate change for years. Japan is also taking similar actions. The aim of the chapter is therefore to present cooperation between Japan and the European Union in the context of climate issues. By presenting an outline of EU and Japanese climate action, political and scientific cooperation in this field, as well as analyzing selected project examples, it will be possible to answer questions about the history of EU-Japan cooperation in the fight against climate change and the nature of this cooperation.